FEMALE SOCIOECOLOGICAL INFRASTRUCTURE IN THE CAATINGA: WOMEN, SOCIAL TECHNOLOGIES, AND BIOCULTURAL RESILIENCE IN THE BRAZILIAN SEMI-ARID - Roberto Ramos, Paulo; Caroline Coelho Leal Árias Amorim, Anne; Cristiane do Nascimento, Deise; Almeida Ferreira, Rodrigo; Bagagi Bezerra, Armando; Colaço de Azevêdo, Arlete; Francisco Alves de Oliveira, Hohenfeld; Alberto de Sá Quirino, Cláudio; Dilmária do Nascimento Lima, Maria; Rodrigues Silva, Jeová; Dias Soares, Cesar; Alan Barbosa Bispo, Italo; et al. (Revista Gênero e Interdisciplinaridade, 2026)
Dryland territories have increasingly become central to global debates on climate adaptation and sustainability. In the Brazilian Semi-Arid region, particularly within the Caatinga biome, socioecological resilience emerges from the interaction between environmental constraints, local knowledge systems, and community-based resource management. However, the role of women in sustaining these adaptive processes often remains underestimated or analytically fragmented in the literature. This study aims to analyze how women’s protagonism contributes to the construction of biocultural resilience in the Caatinga through the adoption and management of social technologies. Methodologically, the research adopts an integrative literature review conducted between October 2025 and February 2026 in the databases Web of Science, Scopus, SciELO, and DOAJ. An initial set of 279 records was identified, from which a final corpus of 25 studies was selected through systematic screening procedures. The results indicate that women play a strategic role in the governance of water resources, agroecological food production, seed conservation, and community organization, forming a network of practices that sustain local socioecological systems. Social technologies such as rainwater harvesting cisterns, agroecological home gardens, and community seed banks strengthen territorial resilience while simultaneously revealing tensions between empowerment and the persistence of gendered labor burdens. The study proposes the concept of female socioecological infrastructure to describe the network of practices, knowledge systems, and social relations through which women sustain ecological and social reproduction in dryland territories. Recognizing these dynamics is essential for developing climate adaptation strategies that integrate gender justice, territorial governance, and socioecological sustainability in the Brazilian Semi-Arid.